1985
DOI: 10.1139/v85-220
|View full text |Cite
|
Sign up to set email alerts
|

Inter-ring dihedral angles in polychlorinated biphenyls from photoelectron spectroscopy

Abstract: A proposal that the physiological activity of a chlorinated biphenyl is related to its degree of molecular planarity is explored through experimental measurements of inter-ring dihedral angles in the gas phase. A known correlation between the difference between fourth and first ionization energies of substituted biphenyls (via photoelectron spectroscopy), and the thermally averaged inter-ring dihedral angle as established by electron diffraction techniques, is confirmed and exploited for the present purpose. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…All fall in the range 37–39 o , which is within the range of values determined for 3,3′-dmbp by photoelectron [46-48] or NMR spectroscopy [49,50]. It is seen also that the C Ar -C Ar -C = O dihedral angle, ϕ, between the carbonyl group and the benzene ring to which it is attached is close to 0 o for 4-Ac and 5-Ac showing that the steric interactions between the 4-Ac group and the neighboring hydrogen and methyl, and between the 5-Ac group and the two neighboring hydrogens, are negligible.…”
Section: Resultssupporting
confidence: 72%
“…All fall in the range 37–39 o , which is within the range of values determined for 3,3′-dmbp by photoelectron [46-48] or NMR spectroscopy [49,50]. It is seen also that the C Ar -C Ar -C = O dihedral angle, ϕ, between the carbonyl group and the benzene ring to which it is attached is close to 0 o for 4-Ac and 5-Ac showing that the steric interactions between the 4-Ac group and the neighboring hydrogen and methyl, and between the 5-Ac group and the two neighboring hydrogens, are negligible.…”
Section: Resultssupporting
confidence: 72%
“…Reference compound 4 has an LE of 0.35, making it a good drug candidate for this metric. From the other compounds in this study, most (16) were in the 0.32 LE 0.38 range. Out of the remaining four, three had a ligand efficiency below 0.30 (8, 9 and 23), and one above 0.4 (10, LE ¼ 0.47).…”
Section: Ligand Efficiency and Lipophilicity [17]mentioning
confidence: 62%
“…An increase in size and lipophilicity in the halogen series also led to similar results (F, 11; Cl, 5; Br, 14; I, 15). In contrast to the analogous cyanopyrimidines, moving the chloro substituent along the ring did not change the affinity much (4-Cl, 5, 5.0 nM; 3-Cl, 16, 12 nM; 2-Cl, 17, 11 nM), which seems to indicate that the dihedral angle between the thiazolyl and phenyl rings does not have a small value (which would be disfavored by the presence of a 2-chloro substituent) [16] in the binding pose. Also, dichlorination on the 3 and 4 position gave a similar affinity (18, 11 nM), which is again in contrast with our previous findings on cyanopyrimidine analogs.…”
Section: Thiazole Substituentmentioning
confidence: 63%
“…Moreover, these authors were the first to suggest that the absolute planarity of PCBs might not be required for effective binding. This hypothesis was supported by ab initio quantum mechanical calculations and crystallography studies that suggested polarizability and electronacceptor properties of the ligands, rather than size and planarity (or coplanarity), can control the affinity of binding to the AhR (11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 91%